Education and Health Expenditures as Determinants of Human Development in Eastern Indonesia - Nugraha, Putu Ananda Devi; Wahyuningsih, Andi Nur; Yusuf, La Ode Muhammad Iksan; Erwin, Erwin (Jurnal Indonesia Sosial Sains, 2025)
This study aims to analyze the partial and simultaneous effects of education and health on the Human Development Index. This study is a quantitative study using Panel data from 2014-2023 in Eastern Indonesia. Then, the data was analyzed using Multiple Ordinary Least Squares (OLS) analysis. The results of the study indicate that the education variable has a positive and significant partial effect on the human development index in Eastern Indonesia. Meanwhile, the health variable does not have a partial effect on the human development index in Eastern Indonesia. Simultaneously, education and health affect the human development index in Eastern Indonesia. The implication of the study is to confirm that improving the quality of education is a key factor in improving the human development index in Eastern Indonesia, while health requires improved service quality and equal access so that it can have a real impact on the development of the human development index in Eastern Indonesia.